Surface Characteristics of Electrospun p-Sulphonated Calix[4]Arene Functionalized Cellulose Acetate Nanofiber and Its Behaviour towards Methylene Blue Adsorption. (9th December 2022) - Basri, Nur Amilah Fadlina; Wahid, Mohd Haniff; Zainal, Zulkarnain; Ahmad, Shahrul Ainliah Alang; Manap, Mohd Rashidi Abdull
Abstract : p -sulphonated calix[4]arene ( p -SOCX) functionalized cellulose acetate/graphene oxide (CA/GO) nanofibers were successfully prepared via the electrospinning technique. The presence of p -SOCX within the fiber matrix was ascertained using Fourier Transform Infrared spectroscopy and Carbon-Hydrogen-Nitrogen-Sulphur elemental analyses. Apparent changes in morphology of the samples were observed under scanning electron microscope where fiber diameters increased with increasing p -SOCX content. Preliminary dye removal test at different pH, dosage, and temperature of functionalized CA/GO nanofiber demonstrates enhanced adsorption capacity of methylene blue in presence of p -SOCX compared to pristine CA nanofiber and CA/GO nanofiber at an optimum pH 8. The highest removal efficiency obtained was 88.84% with initial methylene blue dye concentration of 10 mg/L, adsorbent dosage of 20 mg/10 mL, contact time of 30 min at room temperature ca. 293 K.